2020
DOI: 10.3390/ijerph17020414
|View full text |Cite
|
Sign up to set email alerts
|

The Unholy Trinity: Childhood Trauma, Adulthood Anxiety, and Long-Term Pain

Abstract: Background: Childhood trauma is considered to be a risk factor for developing anxiety as well as chronic pain. The aim of this study was to assess the association between childhood trauma and reporting anxiety and long-term pain conditions in the general and clinical populations. Methods: Respondents from a representative sample in the Czech Republic (n = 1800, mean age: 46.6 years, 48.7% male) and patients with a clinically diagnosed anxiety or adjustment disorder (n = 67, mean age: 40.5 years, 18.0% male) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 58 publications
0
20
0
1
Order By: Relevance
“…The most common serotonergic anxiolytics are the selective serotonin reuptake inhibitors (SSRI) and serotonin norepinephrine reuptake inhibitors (SNRI), and because of their safety profile even in overdose, they are possible substitutes for benzodiazepines in patients with co-occurring anxiety and pain. [24][25][26][27] There are no studies on whether the use of potential substitute drugs (gabapentinoids and SSRIs/SNRIs) increased as opioids and benzodiazepines decreased. We hypothesised that opioid and benzodiazepine prescriptions would decrease while substitute medications, gabapentinoids and SSRIs/SNRIs, would increase in response to the published and widely disseminated 2016 CDC opioid and benzodiazepine guidelines.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The most common serotonergic anxiolytics are the selective serotonin reuptake inhibitors (SSRI) and serotonin norepinephrine reuptake inhibitors (SNRI), and because of their safety profile even in overdose, they are possible substitutes for benzodiazepines in patients with co-occurring anxiety and pain. [24][25][26][27] There are no studies on whether the use of potential substitute drugs (gabapentinoids and SSRIs/SNRIs) increased as opioids and benzodiazepines decreased. We hypothesised that opioid and benzodiazepine prescriptions would decrease while substitute medications, gabapentinoids and SSRIs/SNRIs, would increase in response to the published and widely disseminated 2016 CDC opioid and benzodiazepine guidelines.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The CTQ has been validated in several countries: On representative samples in Germany [ 18 , 19 ], in the Czech Republic [ 20 ], in Memphis, USA [ 21 ], and on clinical samples in Brazil [ 22 ], Spain [ 23 ], the Netherlands [ 24 ], Germany [ 25 ], and Denmark [ 26 ]. The CTQ has also been used in many association studies, e.g., to monitor the associations between childhood trauma experiences and chronic pain and anxiety [ 27 ], substance use disorder in Taiwanese patients [ 28 ], to compare the experiences of trauma in South African women with or without HIV [ 29 ], and to support the idea that childhood trauma experiences and adult attachment style are associated with higher use of negative religious coping strategies [ 30 ]. The CTQ was also used to examine the prevalence of traumatic experiences in South Korean adults [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast with large ACE studies [12][13][14]53] and meta-analytic studies [15,18] confirming links between childhood trauma and various chronic conditions, or between childhood trauma and chronic pain [17,18,58]. In a recent study analyzing the same Czech representative sample, a group of chronic pain conditions (including migraine) with/without anxiety was assessed, and the link between chronic pain and childhood trauma was confirmed [58]. The negative relationship between childhood trauma and no chronic conditions in our study revealed the empirical knowledge and experience that people raised in good conditions early in life, without excessive stress caused by abuse and neglect, are more likely to have good health in later life.…”
Section: Discussionmentioning
confidence: 68%
“…However, in our study, no direct effect was found between childhood trauma and adulthood pain conditions other than migraine and other chronic conditions. This is in contrast with large ACE studies [12][13][14]53] and meta-analytic studies [15,18] confirming links between childhood trauma and various chronic conditions, or between childhood trauma and chronic pain [17,18,58]. In a recent study analyzing the same Czech representative sample, a group of chronic pain conditions (including migraine) with/without anxiety was assessed, and the link between chronic pain and childhood trauma was confirmed [58].…”
Section: Discussionmentioning
confidence: 81%